The case against the link - HABERLER, G. (PSL Quarterly Review, 2014)
The proposal that the creation of international reserves by the IMF be linked with development assistance to less developed countries has become more insistent in recent years. The primary and basic purpose of the Link is to increase the flow of development aid to less developed countries from more developed countries. It is safe to say, however, that if it could be shown that the basic objective cannot be achieved, or only to a small and uncertain extent, the enthusiasm for the Link would quickly die down. While the author does not question the desirability of the basic objective, it is argued that a sizeable increase in the flow of aid cannot be achieved through the Link and that it would be an inefficient method for providing aid. JEL: F35, F33